Retrospective evaluation of moderate‐to‐severe pulmonary hypertension in dogs naturally infected with Angiostrongylus vasorum. (8th December 2014) - Borgeat, K.; Sudunagunta, S.; Kaye, B.; Stern, J.; Luis Fuentes, V.; Connolly, D. J.
<x xml:space="preserve">Abstract</x> OBJECTIVES The outcome in dogs with pulmonary hypertension associated with natural Angiostrongylus vasorum infection is unclear. This study aimed to report long‐term outcome of dogs with A. vasorum and pulmonary hypertension, and to evaluate factors associated with pulmonary hypertension development. It was hypothesised that dogs with pulmonary hypertension had a shorter survival time than dogs without pulmonary hypertension. METHODS Retrospective review of clinical records of dogs diagnosed with A. vasorum. Dogs were classified as having or not having pulmonary hypertension based on clinical signs and imaging findings. Signalment, signs and outcome were recorded. DNA obtained from banked samples was genotyped for the PDE5a:E90K polymorphism, a possible factor in development of pulmonary hypertension. RESULTS The proportion of dogs with moderate‐to‐severe pulmonary hypertension and A. vasorum infection in the study population was 14 · 6%. No difference in the population characteristics or PDE5a genotype was detected between dogs with and without pulmonary hypertension. Dogs with pulmonary hypertension had a significantly shorter survival time (P = 0 · 006) and a greater risk of death within 6 months of diagnosis (odds ratio 12 · 5, 95% confidence interval 2 · 1 to 74 · 9; P = 0 · 0053). CLINICAL SIGNIFICANCE A. vasorum‐associated pulmonary hypertension is an important problem in naturally infected dogs and has a negative effect upon survival.